Results of experimental studies of civil defense structures self-weight pre-stressed continuous three-span steel-reinforced concrete slabs - Hasenko, Anton; Shtanko, Kostiantyn (Academic journal Industrial Machine Building Civil Engineering, 2024)
The paper presents results of experimentally tested samples of resource-saving non-cut three-span steel-reinforced concrete slabs that can be used for the construction of floors of civil defense structures. The specimens differed in the lengths of the concreting grips, which made it possible to study the development of deflections in the extreme and middle spans due to changes in the stiffness of the section at the supports. The length of the concreting section is determined by the points of zero bending moments. During the first stage of concreting, the middle span of the steel structure bends downward due to the concrete mix’s own weight, which causes the extreme sections that are not under load to bend upward. After the concrete of the first stage reaches the design strength, the concrete of the outer spans is concreted. At the same time, the extreme spans bend downward due to the weight of the concrete mixture, forcing the middle span, which already has a steel-reinforced concrete section, to bend upward.